Analisis kandungan energi dan zat gizi makro pada formula enteral non susu berbasis kacang merah (Phaseolus vulgaris) untuk pasien diabetes mellitus tipe II - Ima Yudiyanti; Putri Ronitawati; Mertien Sa'Pang; Rianti Sri Widayati (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Individuals at the age of 40 years face a 6-fold higher risk of developing Type II diabetes. Modification of enteral nutrition is necessary to address nutritional needs in patients with eating difficulties. Nutritional therapy for Type II diabetes patients should focus on controlling blood glucose levels by selecting foods with low glycemic index and high fiber content. Red beans, rich in protein, carbohydrates, and fiber, offer potential benefits in blood glucose control and as a dairy substitute for individuals with cow's milk allergies, making them a viable candidate for hospital-based enteral nutrition.Objectives: This study aims to determine the macronutrient content, flow test, food cost, and organoleptic test of non-dairy liquid food based on local ingredients. The study uses a completely randomized design.Methods: A complete randomized design was employed for this research. Product development activities were conducted in June 2022 at the Nutritional Kitchen of Jantung dan Pembuluh Darah Harapan Kita Hospital. Preparation of non-dairy liquid food using red beans as a base, proximate analysis of nutritional content, flow test through an NGT tube, food cost calculation, and organoleptic assessment involving ten respondents were carried out.Results: Proximate analysis of the formula yielded the following composition: water content 85,88%, ash 0,25%, protein 1,95%, fat 2,343%, carbohydrates 9,60%, and fiber 1,38%. The flow test for the red bean formula through the Fr 16 NGT tube demonstrated a rate of 50cc/31,90 seconds. The calculated food cost for one recipe of red bean formula was Rp. 8,734.00. Organoleptic evaluation results indicated that the majority of respondents favored the aroma (80%), taste (60%), color (100%), and texture (90%).Conclusion: The red bean formula meets the protein and carbohydrate requirements of the diabetes mellitus diet standards, while the fat and fiber content do not yet meet the diabetes mellitus diet standards.